Analysis of the Performance of the Transportation Agency in the Framework of Optimising the Safety Guarantee of Public Transport Passengers in Medan City (Study on Trans Metro Deli Buses) - Hasibuan, Dinda Winsari; Ginting, Simson (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine how the Performance of the Medan City Transportation Agency in the Framework of Optimising the Safety Guarantee of Public Transport Passengers in Medan City (Study on Trans Metro Deli Bus) using descriptive research methods with a qualitative approach. Data collection is done by interview, observation, and documentation techniques. Data were obtained through primary and secondary data and analysed using data reduction, data presentation, and conclusion drawing. The results of this study indicate that the performance of the Medan City Transportation Agency in the context of Optimising the Safety Guarantee of Public Transport Passengers in Medan City has been running well but there is still a need for supervision and a high sense of responsibility for the implementation and running of the Trans Metro Deli Bus and to further improve socialisation and good communication with passengers in order to attract their interest to always use the Bus because it is guaranteed safety, security and comfort.